2023
DOI: 10.1139/cjc-2022-0109
|View full text |Cite
|
Sign up to set email alerts
|

Oligomerization of an ansa-ferrocene with pyrazabole bridge

Abstract: Ansa-ferrocenes with pyrazabole bridges are chemically robust entities and therefore suitable building blocks for the synthesis of rigid-rod polymers that combine redox-active Fe(II) centers and beltene-like  faces. The specific monomers we developed bear OEt groups at both tetracoordinated boron atoms (for solubility reasons) and ethynyl substituents at the 4-positions of the two pyrazole rings. Polymerization was accomplished by a condensation reaction with 1,4-diiodobenzene using a Sonogashira-Hagihara-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Dithienooxadiborepine was chosen because it has high luminous efficiency and is easy to modify, 23a and ACID and NICS calculations have revealed additional stabilization through aromaticity for the dithienodiborepin PAHs. 23b Using Sonogashira coupling 24 and Glaser oxidative coupling reactions carried out under mild conditions, several ethynyl-linked or butadiynyl-linked organoborane oligomers were prepared successfully (Chart 1 and Scheme 1). It was found that the presence of hexyl substituents has a great impact on the structures and properties of the compounds.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Dithienooxadiborepine was chosen because it has high luminous efficiency and is easy to modify, 23a and ACID and NICS calculations have revealed additional stabilization through aromaticity for the dithienodiborepin PAHs. 23b Using Sonogashira coupling 24 and Glaser oxidative coupling reactions carried out under mild conditions, several ethynyl-linked or butadiynyl-linked organoborane oligomers were prepared successfully (Chart 1 and Scheme 1). It was found that the presence of hexyl substituents has a great impact on the structures and properties of the compounds.…”
Section: ■ Introductionmentioning
confidence: 99%
“…6 Several attempts have also been made to incorporate tricoordinate (sp 2 -hybridized) boron atoms into the bridging position of polyferrocenes. 7–10 The synthesis of aminoboranediyl-bridged polyferrocenes, PFB N , was first pursued by Manners and Braunschweig and co-workers via thermal ring-opening polymerization (ROP) of strained 1-amino-1-bora-[1]ferrocenophanes. 7 Recently, Müller and co-workers resumed these studies, resulting in soluble derivatives of this kind by using solubilizing alkyl groups at the ferrocene moieties (R′′).…”
mentioning
confidence: 99%